Efficient adsorbent as well as preparation method and application thereof

By modifying the UiO-66 molecular sieve hydroxyl group and loading it with the modified water glass, an efficient adsorbent was prepared, which solved the problem of difficult to preserve and control volatile heterocyclic fragrances in the prior art, and achieved efficient adsorption and easing of fragrances Controlled release effect.

CN119406383APending Publication Date: 2025-02-11HENAN AGRICULTURAL UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411700382.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively preserve and control volatile heterocyclic fragrances, resulting in limited practical applications.

Method used

By modifying the UiO-66 molecular sieve hydroxyl group to form UiO-66-(OH)2 and loading it with the modified water glass, a high-efficiency adsorbent was prepared to increase the adsorption amount and sustained release of heterocyclic fragrances. Effect.

Benefits of technology

This highly efficient adsorbent significantly improves the adsorption capacity and sustained release effect of heterocyclic fragrances, extends the retention rate of fragrances, and is suitable for slow-release applications of fragrance fragrances.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of controlled release of spices and essences, and discloses an efficient adsorbent as well as a preparation method and application thereof. The preparation method of the efficient adsorbent comprises the following steps: mixing zirconium chloride, 2-hydroxy-1, 4-phthalic acid, a hydrochloric acid solution and N, N-dimethylformamide, and carrying out a reaction to obtain UiO-66-(OH) 2; the preparation method comprises the following steps: mixing water glass, 3-aminopropyltrimethylsilane and toluene, and reacting to obtain modified water glass; and mixing UiO-66-(OH) 2, the modified water glass, ammonia water and an ethanol water solution to obtain the adsorbent. According to the invention, the UiO-66 molecular sieve is subjected to hydroxyl modification, the hydroxyl and the heterocyclic perfume can form a hydrogen bond, a positive promotion effect is achieved for improving the adsorption capacity and prolonging the slow release effect, and meanwhile, the modified water glass and the UiO-66-(OH) 2 are compounded, so that the adsorption capacity of the adsorbent on the heterocyclic perfume is greatly increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sustained and controlled release of spices and flavors, and in particular to a high-efficiency adsorbent and a preparation method and application thereof. Background Art

[0002] While the flavor and fragrance industry is developing rapidly, its sensitive and volatile characteristics have severely limited the practical application of flavors and fragrances, especially nitrogen-containing and oxygen-containing heterocyclic flavors, which generally have low boiling points and are extremely volatile. It is crucial to develop technologies to preserve and control the release of volatile aromatic molecules. Nano-adsorption technology is one of the methods that can effectively increase the utilization rate of flavors and fragrances. In particular, MOFs materials have advantages over other porous adsorption materials due to their clear porous structure, large specific surface area and simple synthesis method.

[0003] Therefore, it is necessary to study the role of MOFs materials in the sustained and controlled release of spices and develop efficient adsorbents for heterocyclic spices. Summary of the invention

[0004] The purpose of the present invention is to provide a high-efficiency adsorbent and a preparation method and application thereof, so as to solve the problems existing in the prior art.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a high-efficiency adsorbent, comprising the following steps:

[0007] Zirconium chloride, 2-hydroxy-1,4-phthalic acid, hydrochloric acid solution and N,N-dimethylformamide are mixed and reacted to obtain UiO-66-(OH)2;

[0008] Mixing water glass, 3-aminopropyltrimethylsilane and toluene, and performing a second reaction to obtain modified water glass;

[0009] UiO-66-(OH)2, modified water glass, ammonia water and ethanol aqueous solution are mixed and dispersed to obtain an adsorbent.

[0010] Preferably, in the above-mentioned method for preparing a highly efficient adsorbent, the mass ratio of zirconium chloride to 2-hydroxy-1,4-phthalic acid is 1-3:1-3;

[0011] The dosage ratio of the zirconium chloride and the hydrochloric acid solution is 1-3 g: 10-20 mL;

[0012] The concentration of the hydrochloric acid solution is 36-38wt%;

[0013] The usage ratio of the zirconium chloride and N,N-dimethylformamide is 1-3 g: 100-200 mL.

[0014] Preferably, in the above-mentioned method for preparing a high-efficiency adsorbent, the temperature of the first reaction is 80 to 100° C., and the time of the first reaction is 12 to 24 hours.

[0015] Preferably, in the above-mentioned method for preparing a highly efficient adsorbent, the volume ratio of water glass, 3-aminopropyltrimethylsilane and toluene is 150-200: 3-4: 100-150;

[0016] The concentration of the water glass is 1.5-2wt%, and the modulus of the water glass is 2.4-3.4.

[0017] Preferably, in the above-mentioned method for preparing a high-efficiency adsorbent, the temperature of the second reaction is 80-90° C., and the time of the second reaction is 8-15 hours.

[0018] Preferably, in the above-mentioned method for preparing a highly efficient adsorbent, the usage ratio of the modified water glass and the ethanol aqueous solution is 0.1-0.5 g: 50-100 mL;

[0019] The concentration of the ethanol aqueous solution is 75-85wt%;

[0020] The mass ratio of UiO-66-(OH)2 to modified water glass is 2-3:0.1-0.5;

[0021] The usage ratio of the modified water glass and ammonia water is 0.1-0.5 g: 4-5 mL;

[0022] The concentration of the ammonia water is 25-28 wt %.

[0023] Preferably, in the above-mentioned method for preparing a high-efficiency adsorbent, the dispersion temperature is 20 to 30° C., and the dispersion time is 4 to 8 hours.

[0024] The invention also provides a high-efficiency adsorbent prepared by a method for preparing the high-efficiency adsorbent.

[0025] The invention also provides an application of a high-efficiency adsorbent in adsorbing heterocyclic fragrances.

[0026] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0027] In the present invention, 2-hydroxy-1,4-phthalic acid is used to modify the hydroxyl group of UiO-66 molecular sieve, and the hydroxyl group of UiO-66-(OH)2 can form hydrogen bonds with heterocyclic spices, which plays a positive role in increasing the adsorption amount and prolonging the sustained release effect; 3-aminopropyltrimethylsilane is used to modify water glass to obtain amino-grafted water glass, that is, modified water glass, and finally the modified water glass and UiO-66-(OH)2 are loaded to obtain an adsorbent; wherein the water glass is composed of oligosilicic acid and high-polysilicic acid, and the oligosilicic acid contains cage structures such as monosilicic acid, chain disilicate, chain trisilicic acid, cyclotetrasilicic acid, cubic octasilicic acid, etc. After the modified water glass is loaded with UiO-66-(OH)2, the secondary pore structure constructed by the cage-structured oligosilicic acids such as cyclotetrasilicic acid and cubic octasilicic acid greatly increases the adsorption capacity of the adsorbent for heterocyclic spices, and at the same time, it is also helpful to increase the sustained release amount. DETAILED DESCRIPTION

[0028] The present invention provides a method for preparing a high-efficiency adsorbent, comprising the following steps:

[0029] Zirconium chloride, 2-hydroxy-1,4-phthalic acid, hydrochloric acid solution and N,N-dimethylformamide are mixed and reacted to obtain UiO-66-(OH)2;

[0030] Mixing water glass, 3-aminopropyltrimethylsilane and toluene, and performing a second reaction to obtain modified water glass;

[0031] UiO-66-(OH)2, modified water glass, ammonia water and ethanol aqueous solution are mixed and dispersed to obtain an adsorbent.

[0032] In the present invention, the mass ratio of the zirconium chloride to 2-hydroxy-1,4-phthalic acid is preferably 1-3:1-3, more preferably 1.2-2:1.2-2.5, and more preferably 1.5-2:1.8-2.2.

[0033] In the present invention, the usage ratio of the zirconium chloride and the hydrochloric acid solution is preferably 1-3 g:10-20 mL, more preferably 1.5-2.5 g:12-18 mL, and more preferably 1.8-2 g:15-16 mL.

[0034] In the present invention, the concentration of the hydrochloric acid solution is preferably 36-38 wt %, more preferably 36.5-37.5 wt %, and more preferably 37 wt %.

[0035] In the present invention, the usage ratio of the zirconium chloride and N,N-dimethylformamide is preferably 1-3 g:100-200 mL, more preferably 1.5-2.5 g:120-180 mL, and more preferably 1.8-2 g:150-160 mL.

[0036] In the present invention, the specific process of mixing zirconium chloride, 2-hydroxy-1,4-phthalic acid, hydrochloric acid solution and N,N-dimethylformamide is as follows:

[0037] First dissolve zirconium chloride in N,N-dimethylformamide, then add 2-hydroxy-1,4-phthalic acid and hydrochloric acid solution and stir until dissolved.

[0038] In the present invention, the temperature of the first reaction is preferably 80-100°C, more preferably 85-98°C, more preferably 90-95°C; the time of the first reaction is preferably 12-24h, more preferably 15-20h, more preferably 16-18h.

[0039] In the present invention, after the first reaction is completed, the following steps are further included:

[0040] The obtained product was washed with N,N-dimethylformamide and anhydrous ethanol in sequence, and then vacuum dried at 80° C. for 12 h.

[0041] In the present invention, the volume ratio of water glass, 3-aminopropyltrimethylsilane and toluene is preferably 150-200:3-4:100-150, more preferably 160-190:3.2-3.8:110-140, and more preferably 170-180:3.3-3.5:120-130.

[0042] In the present invention, the concentration of the water glass is preferably 1.5-2wt%, more preferably 1.6-1.9wt%, more preferably 1.7-1.8wt%; the modulus of the water glass is preferably 2.4-3.4, more preferably 2.5-3.3, more preferably 2.8-3.

[0043] In the present invention, the specific process of mixing water glass, 3-aminopropyltrimethylsilane and toluene is:

[0044] Water glass was mixed with toluene, and then 3-aminopropyltrimethylsilane was added.

[0045] In the present invention, the temperature of the second reaction is preferably 80-90°C, more preferably 82-88°C, more preferably 85-86°C; the time of the second reaction is preferably 8-15h, more preferably 9-14h, more preferably 10-13h.

[0046] In the present invention, after the second reaction is completed, the following steps are further included:

[0047] The obtained product was washed with anhydrous ethanol and distilled water in sequence, and then vacuum dried at 80°C for 12 h.

[0048] In the present invention, the usage ratio of the modified water glass and the ethanol aqueous solution is preferably 0.1-0.5 g:50-100 mL, more preferably 0.2-0.4 g:60-90 mL, and more preferably 0.3 g:70-80 mL.

[0049] In the present invention, the concentration of the ethanol aqueous solution is preferably 75 to 85 wt %, more preferably 78 to 82 wt %, and even more preferably 77 to 80 wt %.

[0050] In the present invention, the mass ratio of UiO-66-(OH)2 to modified water glass is preferably 2-3:0.1-0.5, more preferably 2.2-2.8:0.2-0.4, and more preferably 2.5-2.8:0.25-0.35.

[0051] In the present invention, the usage ratio of the modified water glass and ammonia water is preferably 0.1-0.5 g:4-5 mL, more preferably, and more preferably.

[0052] In the present invention, the concentration of the aqueous ammonia is preferably 25 to 28 wt %, more preferably 25.5 to 27.5 wt %, and even more preferably 26 to 27 wt %.

[0053] In the present invention, the specific process of mixing the UiO-66-(OH)2, modified water glass, ammonia water and ethanol aqueous solution is as follows:

[0054] The modified water glass and ethanol aqueous solution were mixed, and then UiO-66-(OH)2 and ammonia water were added.

[0055] In the present invention, the dispersion temperature is preferably 20 to 30° C., more preferably 22 to 28° C., and more preferably 23 to 25° C.; the dispersion time is preferably 4 to 8 h, more preferably 5 to 7 h, and more preferably 6 h.

[0056] In the present invention, after the dispersion is completed, the method further comprises:

[0057] The obtained product was washed with anhydrous ethanol and acetone in sequence, and then vacuum dried at 80°C for 12 h.

[0058] The invention also provides a high-efficiency adsorbent prepared by a method for preparing the high-efficiency adsorbent.

[0059] The invention also provides an application of a high-efficiency adsorbent in adsorbing heterocyclic fragrances.

[0060] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0061] Example 1

[0062] 1.5 g of zirconium chloride was dissolved in 150 mL of N, N-dimethylformamide, and then 1.68 g of 2-hydroxy-1, 4-phthalic acid and 15 mL of a 37 wt% hydrochloric acid solution were added and stirred until dissolved, and the mixture was reacted at 90° C. for 12 h. After the reaction, the obtained product was washed with N, N-dimethylformamide and anhydrous ethanol in sequence, and then vacuum dried at 80° C. for 12 h to obtain UiO-66-(OH)2;

[0063] 150 mL of 2 wt% water glass (modulus 3.3) was mixed with 150 mL of toluene, and then 3 mL of 3-aminopropyltrimethylsilane was added, and the mixture was reacted at 85° C. for 10 h. After the reaction, the obtained product was washed with anhydrous ethanol and distilled water in sequence, and then vacuum dried at 80° C. for 12 h to obtain modified water glass;

[0064] Mix 0.4 g of modified water glass and 80 mL of 80 wt% ethanol aqueous solution, then add 2.5 g of UiO-66-(OH)2 and 4.5 mL of 27 wt% ammonia water, disperse at room temperature for 6 h, wash with anhydrous ethanol and acetone in turn after dispersion, and vacuum dry at 80 ° C for 12 h to obtain an adsorbent.

[0065] Fragrance adsorption: A watch glass containing 50 mg of the adsorbent prepared in Example 1 and 200 μL of 3-acetylpyridine fragrance was placed in a sealed container, and the container was placed in an oven at 80° C. for full adsorption for 8 hours to obtain an adsorbent / 3-acetylpyridine material. According to the test, the adsorption amount of 3-acetylpyridine fragrance by the adsorbent was 1926.75 mg / g, and the fragrance retention rate was 94.79% after being kept at room temperature for 20 days.

[0066] Example 2

[0067] 1.25 g of zirconium chloride was dissolved in 100 mL of N, N-dimethylformamide, and then 1.42 g of 2-hydroxy-1, 4-phthalic acid and 12 mL of a 37 wt% hydrochloric acid solution were added and stirred until dissolved, and the mixture was reacted at 90° C. for 15 h. After the reaction, the obtained product was washed with N, N-dimethylformamide and anhydrous ethanol in sequence, and then vacuum dried at 80° C. for 12 h to obtain UiO-66-(OH)2;

[0068] 180 mL of 1.5 wt% water glass (modulus of 3.3) was mixed with 150 mL of toluene, and then 3 mL of 3-aminopropyltrimethylsilane was added, and the mixture was reacted at 90° C. for 10 h. After the reaction, the obtained product was washed with anhydrous ethanol and distilled water in sequence, and then vacuum dried at 80° C. for 12 h to obtain modified water glass;

[0069] Mix 0.35 g of modified water glass and 80 mL of 75 wt% ethanol aqueous solution, then add 2 g of UiO-66-(OH)2 and 4 mL of 27 wt% ammonia water, disperse at room temperature for 6 h, wash with anhydrous ethanol and acetone in turn after dispersion, and vacuum dry at 80 ° C for 12 h to obtain an adsorbent.

[0070] Fragrance adsorption: A watch glass containing 50 mg of the adsorbent prepared in Example 2 and 200 μL of 3-acetylpyridine fragrance was placed in a sealed container, and the container was placed in an oven at 80° C. for full adsorption for 8 hours to obtain an adsorbent / 3-acetylpyridine material. According to the test, the adsorption amount of 3-acetylpyridine fragrance by the adsorbent was 1825.69 mg / g, and the fragrance retention rate was 90.23% after being kept at room temperature for 20 days.

[0071] Example 3

[0072] 2.3 g of zirconium chloride was dissolved in 180 mL of N, N-dimethylformamide, and then 2.58 g of 2-hydroxy-1, 4-phthalic acid and 20 mL of a 37 wt% hydrochloric acid solution were added and stirred until dissolved, and the mixture was reacted at 100 ° C for 12 h. After the reaction, the obtained product was washed with N, N-dimethylformamide and anhydrous ethanol in sequence, and then vacuum dried at 80 ° C for 12 h to obtain UiO-66-(OH)2;

[0073] 200 mL of 2 wt% water glass (modulus of 3.3) was mixed with 100 mL of toluene, and then 4 mL of 3-aminopropyltrimethylsilane was added, and the mixture was reacted at 85° C. for 10 h. After the reaction, the obtained product was washed with anhydrous ethanol and distilled water in sequence, and then vacuum dried at 80° C. for 12 h to obtain modified water glass;

[0074] Mix 0.4 g of modified water glass and 60 mL of 80 wt% ethanol aqueous solution, then add 2 g of UiO-66-(OH)2 and 5 mL of 27 wt% ammonia water, disperse at room temperature for 6 h, wash with anhydrous ethanol and acetone in turn after dispersion, and vacuum dry at 80 ° C for 12 h to obtain an adsorbent.

[0075] Fragrance adsorption: A watch glass containing 50 mg of the adsorbent prepared in Example 3 and 200 μL of 3-acetylpyridine fragrance was placed in a sealed container, and the container was placed in an oven at 80° C. for full adsorption for 8 hours to obtain an adsorbent / 3-acetylpyridine material. According to the test, the adsorption amount of 3-acetylpyridine fragrance by the adsorbent was 1724.20 mg / g, and the fragrance retention rate was 88.25% after being kept at room temperature for 20 days.

[0076] Example 4

[0077] 2 g of zirconium chloride was dissolved in 100 mL of N, N-dimethylformamide, and then 2.15 g of 2-hydroxy-1, 4-phthalic acid and 15 mL of a 37 wt% hydrochloric acid solution were added and stirred until dissolved, and the mixture was reacted at 95° C. for 20 h. After the reaction, the obtained product was washed with N, N-dimethylformamide and anhydrous ethanol in sequence, and then vacuum dried at 80° C. for 12 h to obtain UiO-66-(OH)2;

[0078] 150 mL of 2 wt% water glass (modulus of 2.4-3.4) was mixed with 100 mL of toluene, and then 3 mL of 3-aminopropyltrimethylsilane was added, and the mixture was reacted at 82° C. for 15 h. After the reaction, the obtained product was washed with anhydrous ethanol and distilled water in sequence, and then vacuum dried at 80° C. for 12 h to obtain modified water glass;

[0079] Mix 0.5 g of modified water glass and 90 mL of 70 wt% ethanol aqueous solution, then add 3 g of UiO-66-(OH)2 and 5 mL of 27 wt% ammonia water, disperse at room temperature for 6 h, wash with anhydrous ethanol and acetone in turn after dispersion, and vacuum dry at 80 ° C for 12 h to obtain an adsorbent.

[0080] Fragrance adsorption: A watch glass containing 50 mg of the adsorbent prepared in Example 4 and 200 μL of 3-acetylpyridine fragrance was placed in a sealed container, and the container was placed in an oven at 80° C. for full adsorption for 8 hours to obtain an adsorbent / 3-acetylpyridine material. According to the test, the adsorption amount of 3-acetylpyridine fragrance by the adsorbent was 1825.36 mg / g, and the fragrance retention rate was 92.43% after being kept at room temperature for 20 days.

[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-efficiency adsorbent, characterized in that: The following steps are involved: Zirconium chloride, 2-hydroxy-1,4-phthalic acid, hydrochloric acid solution and N,N-dimethylformamide are mixed and reacted to obtain UiO-66-(OH)2; Mixing water glass, 3-aminopropyltrimethylsilane and toluene, and performing a second reaction to obtain modified water glass; UiO-66-(OH)2, modified water glass, ammonia water and ethanol aqueous solution are mixed and dispersed to obtain an adsorbent.

2. The method for preparing a high-efficiency adsorbent according to claim 1, characterized in that: The mass ratio of zirconium chloride to 2-hydroxy-1,4-phthalic acid is 1-3:1-3; The dosage ratio of the zirconium chloride and the hydrochloric acid solution is 1-3 g: 10-20 mL; The concentration of the hydrochloric acid solution is 36-38wt%; The usage ratio of the zirconium chloride and N,N-dimethylformamide is 1-3 g: 100-200 mL.

3. The method for preparing a high-efficiency adsorbent according to claim 2, characterized in that: The temperature of the first reaction is 80-100° C., and the time of the first reaction is 12-24 hours.

4. The method for preparing a high-efficiency adsorbent according to claim 3, characterized in that: The volume ratio of water glass, 3-aminopropyltrimethylsilane and toluene is 150-200:3-4:100-150; The concentration of the water glass is 1.5-2wt%, and the modulus of the water glass is 2.4-3.

4.

5. The method for preparing a high-efficiency adsorbent according to claim 4, characterized in that: The temperature of the second reaction is 80-90° C., and the time of the second reaction is 8-15 hours.

6. The method for preparing a high-efficiency adsorbent according to claim 4 or 5, characterized in that: The usage ratio of the modified water glass and the ethanol aqueous solution is 0.1-0.5 g: 50-100 mL; The concentration of the ethanol aqueous solution is 75-85wt%; The mass ratio of UiO-66-(OH)2 to modified water glass is 2-3:0.1-0.5; The usage ratio of the modified water glass and ammonia water is 0.1-0.5 g: 4-5 mL; The concentration of the ammonia water is 25-28 wt %.

7. The method for preparing a high-efficiency adsorbent according to claim 6, characterized in that: The dispersion temperature is 20-30° C., and the dispersion time is 4-8 hours.

8. A high-efficiency adsorbent obtained by the preparation method of a high-efficiency adsorbent according to any one of claims 1 to 7.

9. Use of the high-efficiency adsorbent according to claim 8 in adsorbing heterocyclic fragrances.